2020
DOI: 10.1155/2020/2960343
|View full text |Cite
|
Sign up to set email alerts
|

Circuitry and Synaptic Dysfunction in Alzheimer’s Disease: A New Tau Hypothesis

Abstract: For more than five decades, the field of Alzheimer’s disease (AD) has focused on two main hypotheses positing amyloid-beta (Aβ) and Tau phosphorylation (pTau) as key pathogenic mediators. In line with these canonical hypotheses, several groups around the world have shown that the synaptotoxicity in AD depends mainly on the increase in pTau levels. Confronting this leading hypothesis, a few years ago, we reported that the increase in phosphorylation levels of dendritic Tau, at its microtubule domain (MD), acts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 101 publications
(298 reference statements)
2
22
0
Order By: Relevance
“…In terms of diagnostic accuracy, the different performance of CSF Ng on MCI ε4− and MCI ε4+ may be due to the fact that less MCI ε4− subjects would progress to AD dementia, while more MCI ε4+ subjects would progress to AD dementia. It is well known that tau protein is mainly distributed in the soma and axons of neurons ( Mandelkow, 1999 ; Wang and Mandelkow, 2016 ; Mondragón-Rodríguez et al, 2020 ). However, recent evidence suggested that tau is also a dendritic protein ( Mondragón-Rodríguez et al, 2012a , b , 2020 ; Regan and Piers, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of diagnostic accuracy, the different performance of CSF Ng on MCI ε4− and MCI ε4+ may be due to the fact that less MCI ε4− subjects would progress to AD dementia, while more MCI ε4+ subjects would progress to AD dementia. It is well known that tau protein is mainly distributed in the soma and axons of neurons ( Mandelkow, 1999 ; Wang and Mandelkow, 2016 ; Mondragón-Rodríguez et al, 2020 ). However, recent evidence suggested that tau is also a dendritic protein ( Mondragón-Rodríguez et al, 2012a , b , 2020 ; Regan and Piers, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that tau protein is mainly distributed in the soma and axons of neurons ( Mandelkow, 1999 ; Wang and Mandelkow, 2016 ; Mondragón-Rodríguez et al, 2020 ). However, recent evidence suggested that tau is also a dendritic protein ( Mondragón-Rodríguez et al, 2012a , b , 2020 ; Regan and Piers, 2015 ). Specifically, under physiological conditions, endogenous tau is located at the postsynaptic of neurons ( Mondragón-Rodríguez et al, 2012b , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations